Effective enterprise architecture (O'Reilly Media, 2019)
"Eben Hewitt (Sabre) shares a holistic approach to enterprise architecture that explains how to bring business architecture, information architecture, data architecture, application architecture, and infrastructure architecture together into a comprehensive design. Eben also demonstrates how to incorporate design thinking principles and work effectively with Agile teams, how architecture can work together with development teams and product management teams, and how to usher your architecture successfully through the value chain. You’ll leave with a practical set of architecture practices that will help you create winning technical architectural designs and communicate them effectively, along with a set of usable templates you can start using immediately to achieve success in your organization."--Resource description page.